Early History of Space Science Department at Rice University—An Autobiographical Account. Issue 1 (20th May 2022) - Dessler, Alexander J.
Abstract: Why a Space Science Department at Rice? A one sentence answer: Because President Kennedy came to Rice University to give a speech about the US going to the Moon, and Rice's President decided that Rice should show a response. Key Points: A unique perspective is provided on the origins of the U.S. space race with the Soviet Union An interesting set of factors were involved in the establishment of Johnson Space Center in Houston and Rice University's role in it The origins of research into Space Weather resulted from several chance factors and took several unpredicted turns